Anesthetic Maintenance of Thyroid Surgery - A. A. Negovsky; T. I. Shpazhnikova; A. A. Znamensky; M. N. Zamyatin (Общая реаниматология)
Thyroid diseases are most common in endocrinology. Thyrotoxicosis induces dysfunction of virtually all organs and systems, the blood circulatory system being subjected to considerable changes. Cardiovascular diseases affect not only the quality of life in a patient, but significantly increase a risk from surgery that is the only radical treatment. For this reason, most authors consider thyrotoxicosis to be a contraindication to elective surgical intervention. At the same time it is known that drug compensation of thyrotoxicosis may be attained in not all patients. In this case, the results of treatment and a patient’s safety during surgery depend on the type and quality of anesthetic protection. The capabilities of anesthetic maintenance of thyroid surgery have recently expanded substantially. The paper deals with the preparation of patients with thyrotoxicosis for surgical intervention and the perioperative management of these patients. Key words: thyroid, toxic goiter, thyrotoxicosis, premedication, anesthetic mode, sevoflurane, xenon.